EFEKTIVITAS PENGGUNAAN ALAT PERAGA EKOSISTEM UNTUK MENINGKATKAN LITERASI SAINS PESERTA DIDIK KELAS V SD NEGERI INPRES BERTINGKAT WAENA - Fadhli, Yongki Dwi; Lusia Narsia Amsad; Yan Dirk Wabiser; Ardian Hangga Kelana; Sakka Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the use of ecosystem teaching aids on improving the scientific literacy of fifth-grade students of SD Negeri Inpres Bertingkat Waena. Scientific literacy is an important skill that every student must have in order to understand scientific concepts and use them to solve problems in everyday life. One effort that can be done to improve scientific literacy is by using contextual and meaningful learning resources such as ecosystem teaching aids. This quantitative study used a pre-experimental design with a One-Group Pretest-Posttest Design pattern. The research sample was carried out in Class V A of SD Negeri Inpres Bertingkat Waena with a total of 30 students. The research instrument was a scientific literacy test in the form of multiple-choice questions implemented before (pretest) and after (posttest) treatment using ecosystem teaching aids. The results of data analysis showed an increase in students' scientific literacy scores after the application of ecosystem teaching aids. This increase was measured using N-Gain (Normalized Gain). The average N-gain value was 0.62, so it was included in the moderate category. Based on these results, it can be concluded that the use of ecosystem teaching aids has proven effective in improving the scientific literacy of Class V A students at Waena State Elementary School.